Earnings Instability and Earnings Inequality of Males in the United States: 1967–1991 - Haider, Steven J. (Journal of Labor Economics, 2001)
Although much research has focused on recent increases in annual earnings inequality in the United States, the increases could have come from either of two sources: the distribution of lifetime earnings could have become more unequal or the receipt of lifetime earnings could have become more unstable. Based on an analysis of the 1968–92 Panel Study of Income Dynamics, we find that lifetime earnings inequality increased during the early 1980s and that earnings instability increased during the 1970s. We also examine how these trends are related to changes in the distribution of wages and hours and the returns to education.